Integration of Islamic and Indonesian Education in the Perspective of KH. Salahuddin Wahid - Rosyidin, Muhammad; Arifin, Imron (Jurnal Pendidikan Agama Islam, 2021)
Islam and Indonesia have been integrated since Islam entered into Nusantara (the Indonesian Archipelago) before Indonesia's independence. This combination has influenced the dynamics of the life of Muslims in Indonesia, including its influence on education issues. The researcher is interested in comprehending the extent of the integration, viewed from the perspective of KH. Salahuddin Wahid. This research focuses on two issues, (1) the thought of KH Salahuddin Wahid about Islamic and Indonesianness and (2) the integration of Islamic and Indonesian education, from the perspective of KH. Salahuddin Wahid. This study used a qualitative approach to literature study with descriptive-analytical data analysis. The research design used is to carry out a literature study by the discussion and to conduct the necessary interviews to complete the data with several informants. The next step is to reduce the data obtained, analyze it, and obtain conclusions according to the focus of the study. The results of this study indicate that in education, integration occurs in various approaches, including, (1) internalizing religious values ​​taught in Islamic religious education, (2) strengthening character and moral education through Islamic religious education, (3) combining religious and non-religious education and discarding the dichotomy of the two, it means combining Islamic education with national education, (4) combining Islamic religious education with science and technology, (5) leveling Islamic boarding schools (pesantren) and improving their quality in order to compete with non-Islamic boarding schools, (6) promoting Islamic history education in Indonesia and its figures, through books, monuments such as museums, as well as educational films, (7) promoting Aswaja and NU education which is following the teachings of the scholars, especially KH. Hasyim Asy'ari, as a character who has successfully combined Islam and Indonesia.